2020
DOI: 10.3390/app10228157
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bonding Performance of Modern Self-Adhesive Resin Cements and Conventional Resin-Modified Glass Ionomer Cements to Prosthetic Substrates

Abstract: This study aimed at evaluating the shear bond strength (SBS) of modern self-adhesive resin cements and resin-modified glass ionomer cements applied to different prosthetic substrates. Zirconia, lithium-disilicate glass-ceramic and a noble metal alloy were used as bonding substrates. They were all sand-blasted with alumina, while LD was further etched with 9.6% hydrofluoric acid (10 s). A light-curing resin-modified glass ionomer cement (3M-GIC: Ketac Cem Plus) and a self-curing resin-modified glass ionomer cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Micro-shear bond strength tests evaluate the adherence of luting materials and the mechanical behaviour of dental ceramics under a load that induces uniform stress concentration at the adhesive interfaces to determine the weakest area between the bonded surfaces [ 27 ]. In their studies, Farag, Maño and Sarahneh observed that reducing the size of bonded interfaces decreases the frequency of the defects and undesirable variations in the specimens and obtained lesser cohesive failures [ 28 , 29 , 30 ]. The stress distribution in the tested samples may be affected by many variables related to the fabrication of specimens, such as the type of cement, the application and the thickness of the cement layer, and also by the testing parameters, such as the distance from the testing device to the cement cylinder or the angle of force application [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Micro-shear bond strength tests evaluate the adherence of luting materials and the mechanical behaviour of dental ceramics under a load that induces uniform stress concentration at the adhesive interfaces to determine the weakest area between the bonded surfaces [ 27 ]. In their studies, Farag, Maño and Sarahneh observed that reducing the size of bonded interfaces decreases the frequency of the defects and undesirable variations in the specimens and obtained lesser cohesive failures [ 28 , 29 , 30 ]. The stress distribution in the tested samples may be affected by many variables related to the fabrication of specimens, such as the type of cement, the application and the thickness of the cement layer, and also by the testing parameters, such as the distance from the testing device to the cement cylinder or the angle of force application [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the fact that the LU presented different values after the surface treatment may be related to the empty spaces and the irregular, rougher surface created by sandblasting, as also observed by other authors [ 13 , 18 ]. However, it should be mentioned that sandblasting may damage the CAD–CAM surface depending on the composition of the CAD–CAM material [ 32 , 33 ]. The findings obtained in our study regarding EDS analysis may not be conclusive, as in several scenarios, no differences in the bonding performance were observed between each material using different luting agents.…”
Section: Discussionmentioning
confidence: 99%
“…The LCCS is characterized with a bifunctional adhesion function; (a) chemical bonding with lithium disilicate glass-ceramics through siloxane bonds; (b) co-polymerization of the monomers within the self-adhesive resin cement through methacrylate groups. [ 20 ] In addition, Mano et al ,[ 21 ] reported that after 5,000 thermocycles of age, the presence of LCCS in self-adhesive resin cement is important for achieving long-term bond ability in lithium disilicate glass-ceramic.…”
Section: Discussionmentioning
confidence: 99%